Independent causal effect of migraines on Alzheimer’s disease risk: a multivariate Mendelian randomization study - Xu, Chengfeng; Wu, Wen; Fan, Yuchao; Zhu, Shuying (Frontiers in Neurology, 2024)
Background: The observational studies investigated the impact of migraine on Alzheimer's Disease (AD). However, these findings were limited by confounding factors and reverse causation, leading to contradictory results. Methods: We utilized Univariable Mendelian Randomization (UVMR) to explore the link between migraine (13,971 cases/470,627 controls) and AD risk (Bellenguez C et al, 39,106 cases/46,828 controls; FinnGen, 111,471 cases/111,471 controls). Meta-analysis was performed for comprehensive synthesis. Employing Multivariable Mendelian Randomization (MVMR), we created models incorporating migraine and 35 potential AD risk factors, examining migraine's independent impact on AD onset risk under considering these factors. Results: The meta-analysis of inverse variance weighted MR results, combining data from Bellenguez C et al. (odds ratio OR [95% confidence interval (CI)]: 1.5717 [1.1868−2.0814], P = 0.0016), p-value = 0.0016) and FinnGen (OR [95% CI]: 1.2904 [0.5419−3.0730], P = 0.5646), provided evidence for a causal relationship between genetically predicted migraine and the heightened risk of AD occurrence ( OR [95% CI]: 1.54 [1.18, 2.00], P < 0.01). After adjusting for Diastolic blood pressure (OR [95% CI]: 1.4120 [0.8487 - 2.3493 ], P = 0.1840) and Tumor necrosis factor alpha (OR [95% CI]: 1.2411 [0.8352 - 1.8443], P = 0.2852), no discernible association was detected between migraine and the risk of AD. Conclusion: This study offers compelling evidence indicating a significant correlation between genetically predicted migraine and an elevated risk of AD.